VD_FINDINFO HC / 2017 / 69 vom 29. Dezember 2016 - VD Tribunal cantonal (2016)
CONTRAT DE TRAVAIL, RÉSILIATION EN TEMPS INOPPORTUN, CERTIFICAT MÉDICAL | 336c CO, 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 308 al. 1 let. a CPC (CH)